Precise Acetabular Prosthesis Positioning Using a Novel Robot‐Assisted Total Hip Arthroplasty System: A Multicenter, Randomized Controlled Trial - Xiao Geng; Ziyang Dong; Yang Li; Minwei Zhao; Yanqing Liu; Zijian Li; Hong Cai; Ming Zhang; Xinfeng Yan; Zhiwen Sun; Xin Lv; Feng Guo; et al. (Orthopaedic Surgery)
ABSTRACT Objective Total hip arthroplasty (THA) is currently one of the most effective treatment methods for end‐stage hip joint disease, and its long‐term effectiveness largely depends on the accurate placement of the acetabular prosthesis. In conventional surgery, the placement of the acetabular prosthesis mainly relies on the surgeon's clinical experience and surgical techniques. To further improve the accuracy of prosthesis placement, a new robotic system for THA is designed. The purpose of this study is to verify the effectiveness and safety of THA assisted by this robotic system. Method A multicenter, prospective, randomized controlled, superiority study design was adopted with statistical methods of t test and Chi‐squared test. Participants undergoing primary THA have been enrolled in three centers of joint surgery in China since July 17, 2023. Robotic THA was operated in the experimental group, and conventional instruments were used in the control group. The primary outcome is the proportion of anteversion and inclination angles in the safe zone. The secondary outcomes include operation time, WOMAC score, Harris score, SF‐36 health questionnaire, dislocation rate of hip joint, and rates of adverse events and serious adverse events. Results A total of 138 patients were included in this study. The proportion of both anteversion and inclination angles in the safe zone was 92.2% in the experimental group and 50.8% in the control group, with significant difference (p < 0.01). The average operation time in the experimental group and control group was 116.4 and 80.5 min respectively, with significant difference (p < 0.01). There was no significant difference in WOMAC score, Harris score, and SF‐36 between the two groups (6 ± 2) weeks after operation (p > 0.05). The dislocation rate of hip joint in the experimental group and control group were 3.0% and 1.5%, respectively, without significant difference (p > 0.05). The rate of adverse events and severe adverse events in the experimental group and control group also showed no significant difference (p > 0.05). No adverse events or serious adverse events were judged to be “definitely related” to the experimental instruments. Conclusion Robotic THA could prolong the operation time within an acceptable range, but more precise acetabular prosthesis positioning could be obtained when compared with conventional surgery. Besides, no significant difference was found in function scores, dislocation rate or other adverse events, which indicates that this new robot system shows both good effectiveness and safety in THA. Trial Registration Clinical Trials: NCT05947734